Pengembangan e-modul fisika terintegrasi STEM untuk meningkatkan keterampilan abad ke-21 siswa kelas XI SMA - Naurah Nazifah; Asrizal Asrizal (Jurnal Penelitian Pendidikan IPA, 2022)
In the current era of the industrial revolution 4.0, students are required to have 21st century skills. The 21st century skills in question are students mastering the 4C skills, that are Communication, Collaboration, Critical thinking and Creativity skills. These four skills must be possessed by students to face the world in the 21st century. One of the current learning approaches that strongly supports the achievement of 21st century skills is STEM-based learning (Science, Technology, Engineering, and Mathematics). In supporting the interdisciplinary success of STEM in physics learning, it is necessary to have effective teaching materials, one of which is a module that students can use independently. In this case, the product developed is an integrated STEM physics e-module to improve the 21st century skills of class XI high school students. The e-module was developed using Flip PDF Professional software with reference to the plomp model. This research is carried out until the development or prototype stage. The research results obtained are the development of STEM integrated physics e-modules to improve students' 21st century skills which have been developed to be valid and practical to use in learning